Effectiveness Of Financial Performance Through Cash Flow Ratio Analysis (Study Case At PT Furniture Gresik) - Nazella Swantana; Anita Akhirruddin (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study analyzes the cash flow management of PT Furniture Gresik using a quantitative descriptive approach. The focus of this research is to evaluate the effectiveness of the company's fund management through the analysis of financial statements, including cash flow statements, balance sheets, and profit and loss. Data was collected through interviews with the Head of Administrative Manager and Finance Department Staff, documentation, such as the company's daily financial and cash reports. The results showed that PT Furniture Gresik has largely complied with the GENERAL SAK in the preparation of financial statements, with several appropriate components, such as the balance sheet, profit and loss, and cash flow. However, there are some shortcomings, such as unrecorded liabilities that require estimation and incomplete financial disclosures. The cash flow ratio analysis shows fluctuations between 2022 and 2023, with a decrease in the operating cash flow and fund flow coverage ratios, despite an increase in cash to interest. These findings provide an important insight into the company's financial condition and the importance of efficient cash flow management to support the continuity and growth of the company.